The Influence of Organizational Justice and Organizational Commitment on The Performance of Employees at The Central Statistical Agency, Kendari City - Sahyunu (International Journal of Management and Education in Human Development, 2023)
The objectives to be achieved in this study are to: examine and explain the simultaneous effect of organizational justice and organizational commitment on employee performance of the Kendari City Central Bureau of Statistics. Testing and explaining the influence of the Leader-Member Exchange on the performance of the Kendari City Central Bureau of Statistics employees. Organizational Justice on Employees Performance of the Kendari City Central Bureau of Statistics and Organizational Commitment on Employees Performance of the Kendari City Central Bureau of Statistics. The population in this study were all Kendari City Central Statistics Agency employees, all of whom were civil servants, totaling 5 4 employees. Measurement of data in this study using a Likert scale. The data analysis technique used in this study is descriptive statistical data analysis and inferential statistics, namely multiple linear regression analysis using SPSS Version 20 software. This study showed that Organizational Justice and Organizational Commitment simultaneously positively and significantly affect employee performance. Organizational justice has a positive impact on employee performance. It means that the increase in employee organizational justice significantly contributes to employee performance. Organizational commitment has a positive but not significant effect on employee performance.